A survey of needle sticks and other sharp injuries among dental undergraduate students - Jaber, Mohamed Abdullah (International Journal of Infection Control, 2011)
Health-care workers' (HCWs') including Dental students’ are at occupational risk of exposure to blood-borne viruses (BBV) following needle sticks and sharp injuries (NSIs). The purpose of this study was to determine the prevalence of NSIs among dental students and evaluate the circumstances in acquiring such injuries. A survey was carried out of all clinical dental students in the College of Dentistry, Ajman University of Science and Technology, United Arab Emirate (UAE) by means of an anonymous self-administered questionnaire that asked questions on demography, number, type, level of knowledge of inoculation injuries and associated risks of exposure to BBV, management and reporting of such exposures. Of 230 Dental students responded to the questionnaire (response rate of 92 percent), 64 (27.9%) were males and 166 (72.1%) were females, 132 (57.3%) were 4th year students and 98 (42.7%) from 5th year students. Of the total sample, 53 students reported having received an inoculation injury, resulting in a 0.23 sharp injury events per student per year. Recapping a needle, administering local anesthesia and performing scaling and polishing procedures were the most important causes of NSIs among dental students 60.3% (32/53). Despite a comprehensive educational programme and training for dental students, knowledge of inoculation injuries and associated issues remained inadequate. The findings of this study confirm that dental students experience NSIs but are not likely to report them, thus it is important that the principles of infection control training and reporting of all NSIs continue to be emphasized throughout undergraduate dental education.